Analisis Strategi Content Marketing Pada Bisnis Kuliner (Studi Kasus Pada Akun Instagram @initempeid) - Ayu Satya Kartika (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
Technology in this digital era creates many ways and tools to help businesses grow faster. Many of the business industries use Instagram as one of the social media platform to boost the market demand. In the food industry especially in small medium enterprises use Instagram to create content marketing strategies. Initempe as local SMEs has implemented the plan to follow their target market lifestyle. This study aims to determine the analysis of content marketing strategy in the food industry (case study in @initempeid Instagram account) by using qualitative research methods and analysis through the theories. The subject of this research is Instagram Initempeid and the object of this research is content marketing in the Initempeid Instagram account. The author uses the data validity research through observations on Instagram Initempeid and conducted interviews with the Owner and Content Creator of Initempeid also the author did the documentation. The results of the study show that several things must be considered in conducting content marketing aimed at promotion, namely by determining target consumers and platforms that suit them. Natural content with good video quality can increase public trust in an account, then consistency in scheduling to upload content is one of the strategies to maintain an audience, and creating classes, activities or events, and collaborations can add opportunities to increase the reach of the account.